EKSPLORASI FAKTOR PENGARUH MINAT PERILAKU KONSUMEN TERHADAP ASURANSI SYARIAH - Meitia Ivanka; Zainarti Zainarti (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Every insurance company hopes to achieve its goals and achieve success. There is a big possibility that this success can be realized by several factors, including affordable insurance premiums, continuous promotions and good service quality. This research aims to analyze the factors that influence public interest in sharia insurance. The research sample involved respondents from various levels of society who have the potential to use sharia insurance. It is hoped that the research results will provide deeper insight into the factors that influence interest in sharia insurance products